Molecular epidemiology of nontyphoidal Salmonella in poultry and poultry products in India: implications for human health - Saravanan, Sellappan; Purushothaman, Venketaraman; Murthy, Thippichettypalayam Ramasamy Gopala; Sukumar, Kuppannan; Srinivasan, Palani; Gowthaman, Vasudevan; Balusamy, Mohan; Atterbury, Robert J.; Kuchipudi, Suresh V. (Springer, 2015)
Human infections with non-typhoidal Salmonella (NTS) serovars are increasingly becoming a threat to human health globally. While all motile Salmonellae have zoonotic potential, Salmonella Enteritidis and Salmonella Typhimurium are most commonly associated with human disease, for which poultry are a major source. Despite the increasing number of human NTS infections, the epidemiology of NTS in poultry in India has not been fully understood. Hence, as a first step, we carried out epidemiological analysis to establish the incidence of NTS in poultry to evaluate the risk to human health. A total of 1215 samples (including poultry meat, tissues, egg and environmental samples) were collected from 154 commercial layer farms from southern India and screened for NTS. Following identification by cultural and biochemical methods, Salmonella isolates were further characterized by multiplex PCR, allele-specific PCR, enterobacterial repetitive intergenic consensus (ERIC) PCR and pulse field gel electrophoresis (PFGE). In the present study, 21/1215 (1.73 %) samples tested positive for NTS. We found 12/392 (3.06 %) of tissue samples, 7/460 (1.52 %) of poultry products, and 2/363 (0.55 %) of environmental samples tested positive for NTS. All the Salmonella isolates were resistant to oxytetracycline, which is routinely used as poultry feed additive. The multiplex PCR results allowed 16/21 isolates to be classified as S. Typhimurium, and five isolates as S. Enteritidis. Of the five S. Enteritidis isolates, four were identified as group D Salmonella by allele-specific PCR. All of the isolates produced different banding patterns in ERIC PCR. Of the thirteen macro restriction profiles (MRPs) obtained by PFGE, MRP 6 was predominant which included 6 (21 %) isolates. In conclusion, the findings of the study revealed higher incidence of contamination of NTS Salmonella in poultry tissue and animal protein sources used for poultry. The results of the study warrants further investigation on different type of animal feed sources, food market chains, processing plants, live bird markets etc., to evaluate the risk factors, transmission and effective control measures of human Salmonella infection from poultry products.